State-of-Charge Estimation of Li-ion Battery at Variable Ambient Temperature with Gated Recurrent Unit Network - Hannan M.A.; How D.N.T.; Mansor M.; Lipu M.S.H.; Ker P.J.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); Deep learning; Learning systems; Lithium compounds; Lithium-ion batteries; Long short-term memory; Multilayer neural networks; Temperature; Empirical evaluations; Experiment set-up; Hyper-parameter; Learning methods; Multi layer perceptron; Simple recurrent networks; State of charge; State-of-charge estimation; Battery management systems